Presynaptic muscarinic receptors and the release of acetylcholine from cerebrocortical prisms: roles of Ca2+ and K+ concentrations - Dolezal, V; Tucek, S (Naunyn-Schmiedeberg's archives of pharmacology, 1993)
The mechanism by which presynaptic muscarinic autoreceptors inhibit the release of acetylcholine (ACh) from cerebrocortical cholinergic fibres has not been clarified. To test the view that muscarinic autoreceptors act by decreasing Ca2+ influx, we performed experiments in which rat cerebrocortical prisms were preloaded with (14C)choline, washed, depolarized with 14-65 mM K+ in the absence of Ca2+ and then exposed (still under depolarization) to various concentrations of Ca2+ to evoke the release of (14C)ACh. The muscarinic agonist, oxotremorine, used at a 100 microM concentration, inhibited the release of (14C)ACh by 59-86% in experiments with 14 and 26.5 mM K+ but had no significant effect at 65.5 mM K+. No systematic changes in the inhibitory effects of oxotremorine could be found at any of the K+ concentrations used when the concentration of Ca2+ was varied in the range of 0.25-4.0 mM. At 2 mM Ca2+ and K+ concentrations above 14 mM, the inhibitory effect of oxotremorine was inversely related to the concentration of K+. The inhibitory effect of oxotremorine on (14C)ACh release was not blocked by 100 microM 4-amino-pyridine. The fact that the inhibitory effect of oxotremorine could not be overcome by an increase in the concentration of Ca2+ suggests that, under the conditions used, a restriction of the influx of Ca2+ did not play a major role in the muscarinic inhibition of ACh release; rather, oxotremorine appeared to act by decreasing membrane depolarization.2+ of the Ca(2+)-voltage hypothesis of neurotransmitter release, supposing
Keywords: nervová zakončení; Potassium; In Vitro Techniques; Rats; Acetylcholine; receptory presynaptické; draslík; Atropine; acetylcholin; vápník; Rats, Wistar; mužské pohlaví; receptory muskarinové; Choline; oxotremorin; techniky in vitro; krysa rodu Rattus; Calcium; Receptors, Muscarinic; mozková kůra; Oxotremorine; zvířata; Tetrodotoxin; Cerebral Cortex; cholin; atropin; potkani Wistar; tetrodotoxin; Nerve Endings; Receptors, Presynaptic; Male; Animals